IFAD programmes with special emphasis on Youth and Women - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Kanayo F. Nwanze, President of International Fund for Agricultural Development (IFAD) talks about the IFAD investments, particularly - "Women in Agriculture" "Youth in Agriculture" and "Youth in Business" The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/